Digital Business Student Development for Entrepreneurs with Software - Nanda Septiani; Ankur Singh Bist; Cicilia Sriliasta Bangun; Ellen Dolan (Pandawan Sejahtera Indonesia, 2022)
Era revolution 4.0, universities throughout Indonesia are computer technology and the economy. This article provides sufficient detail about the course's pedagogical design and practical implementation to serve as a model for how entrepreneurship and business issues can be integrated into a software engineering program. Courses are evaluated using learning diaries and questionnaires, as well as principal lecturer learning in each of the three sample courses The aim of this course is to provide students with an introduction to lean startup methods for ideas/innovations and further product and company development. This course will teach students about the software industry, entrepreneurship, teamwork, and lean startup methodologies and This article provides sufficient detail about the course's pedagogical design and practical implementation to serve as a model for the Course to be evaluated using learning and questionnaires.